Pengaruh Aktivitas Pemberdayaan Perempuan Terhadap Aspek Ekonomi di Desa Wisata Ponggok, Kabupaten Klaten - Rizki Pratama Ningrum; Mohammmad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The existence of Ponggok Tourism Village, located in Polanharjo District, Klaten Regency. As well as abundant potential can be a solution to create the development of women's empowerment programs because it adds opportunities and includes the role of women in all development activities in the field of tourism to take advantage of the existing potential. Women can have a role in several activity programs such as SMEs or other business groups and contribute income to households. Based on this phenomenon, the research question arises "How does the influence of women's empowerment activities in economic aspects in the Ponggok Tourism Village?". This study aims to examine the empowerment of women who experienced development after the existence of the Ponggok Tourism Village. The research method used is quantitative which is supported by qualitative methods. The type of data collected is primary data, obtained through interviews and field observations, and secondary data obtained through literature review and document analysis. The output of this study shows that women's empowerment activities affect the individual women involved and encourage these women to be able to apply further empowerment to other women's empowerment programs and bring other positive impacts because they create jobs and increase the ability of women to do business in economic aspects